Phytotherapy in diabetes: a review of plant - Kuc, Monika; Cyboran, Katarzyna; Machaj, Damian; Korzec, Tomasz; Kania, Konrad (Journal of Education, Health and Sport, 2021)
More than 200 species of plants possess antidiabetic properties which were evaluated mostly by screening tests without digging far for the exact mode of action. Searching among the different literature resources and various database, this article provides a comprehensive review on the available antidiabetic plants that have been approved by pharmacological and clinical evaluations, and which their mechanism(s) of action is assured.